T CD3+CD8+ Lymphocytes Are More Susceptible for Apoptosis in the First Trimester of Normal Human Pregnancy. (17th July 2014) - Darmochwal-Kolarz, Dorota; Sobczak, Ewelina; Pozarowski, Piotr; Kolarz, Bogdan; Rolinski, Jacek; Oleszczuk, Jan
Abstract : Aims. Normal human pregnancy is a complex process of many immunoregulatory mechanisms which protect fetus from the activation of the maternal immune system. The aim of the study was to investigate the apoptosis of lymphocytes in peripheral blood of normal pregnant patients and healthy nonpregnant women. Methods. Sixty pregnant women and 17 nonpregnant women were included in the study. Lymphocytes were isolated and labeled with anti-CD3, anti-CD4, and anti-CD8 monoclonal antibodies. Apoptosis was detected by CMXRos staining and analyzed using the flow cytometric method. Results. We found significantly higher apoptosis of total lymphocytes in peripheral blood of pregnant patients when compared to healthy nonpregnant women. The percentage of apoptotic T CD3 + CD8 + cells in the first trimester was significantly higher when compared to the third trimester of normal pregnancy. The ratio of T CD3 + CD4 +  : T CD3 + CD8 + apoptotic lymphocytes was significantly lower in the first trimester when compared to other trimesters of pregnancy and to both of the phases of the menstrual cycle. Conclusions. The higher apoptosis of T CD3 + CD8 + lymphocytes and the lower ratio of T CD3 + CD4 +  : T CD3 + CD8 + apoptotic cells in the first trimester of normal pregnancy may suggest a higher susceptibility of T CD3 + CD8 + cells for apoptosis as a protective mechanism at the early stage of pregnancy.